Behavioural Problems in School (Training and Practice : Journal of Educational Sciences, 2012)
In recent years, practicing teachers have had to face very serious problems ahead. It is often impossible to implement effective educational tasks, because of the inadequate behaviour of students in the classroom. Many coarse examples can be seen for indiscipline in the classroom, the toolbox of the teachers is less fit for this problem. The author examined the behaviour problems which usually occur in the classroom, and the way how teachers manage these. He proposes recommendations on the occurring behavioural problems in a new and effective way.